Boom, Bust, and Failures to Learn in Experimental Markets - Paich, Mark; Sterman, John D. (Management Science, 1993)
Boom and bust is a pervasive dynamic for new products. Word of mouth, marketing, and learning curve effects can fuel rapid growth, often leading to overcapacity, price war, and bankruptcy. Previous experiments suggest such dysfunctional behavior can be caused by systematic “misperceptions of feedback,” where decision makers do not adequately account for critical feedbacks, time delays, and nonlinearities which condition system dynamics. However, prior studies often failed to vary the strength of these feedbacks as treatments, omitted market processes, and failed to allow for learning. A decision making task portraying new product dynamics is used to test the theory by varying the strength of key feedback processes in a simulated market. Subjects performed the task repeatedly, encouraging learning. Nevertheless, performance relative to potential is poor and is severely degraded when the feedback complexity of the environment is high, supporting the misperception of feedback hypothesis. The negative effects of feedback complexity on performance were not moderated by experience, even though average performance improved. Models of the subjects' decision making heuristics are estimated; changes over trials in estimated cue weights explain why subjects improve on average but fail to gain insight into the dynamics of the system. Though conditions for learning are excellent, experience does not appear to mitigate the misperceptions of feedback or systematic dysfunction they cause in dynamic decision making tasks. We discuss implications for educational use of simulations and games.